THE EFFECT OF TRAINING, WORKFORCE, AND WORK EXPERIENCE ON FARMERS' PRODUCTIVITY IN KENTEN LAUT VILLAGE - Fitriah; Fauziah Afriyani; Budi Setiawan (Universitas KH. Abdul Chalim Mojokerto, 2026)
The purpose of this study is to analyze the effect of training, labor, and work experience on farmer productivity in Kenten Laut Village, Banyuasin Regency. The type of research used is quantitative research with a survey method. The research population consisted of 117 active farmers, while the sample was determined using the Slovin formula so that 91 respondents were obtained. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of IBM SPSS version 29. The results showed that partially training had a positive and significant effect on farmer productivity with t count 2,509 > t table 1,987. Labor has a positive but not significant effect on productivity with t count 1.019 < t table 1.987, which indicates that increased productivity is not only determined by the number of workers, but also the quality and effectiveness of their utilization. Work experience has a positive and significant effect and is the most dominant variable with t count 8.626 > t table 1.987. Simultaneously, training, labor, and work experience have a significant effect on farmer productivity with the result F count 138.928 > F table 2.71. The correlation coefficient (R) of 0.910 indicates that the relationship between training, labor, and work experience on farmer productivity is classified as very strong. The coefficient of determination (R 2 ) shows that the three variables are able to explain farmer productivity by 82.7%, while the rest is influenced by other factors outside the research.